Awareness and Perception of Shrimp Farmers on Feeds and Feed Management - M.K., Kumaran; N., Kalaimani; D., Deboral Vimala (Fishery Technology, 2025)
The study reports results of the survey on shrimp farmers regarding awareness on feeds and feed management. 60% of the farmers has moderate and 32% of them had good awareness about feeds and their management. The respondents perceived that availability and cost of feed were high. However, it was felt that the respondents needed guidance on better feed management practices through extensive education programmes.